97.0k views
5 votes
Which epression is equivalent to (x^4/3 x^2/3)^1/3

User Larspars
by
6.0k points

1 Answer

2 votes

Answer:

The correct answer is X²/³

Explanation:

Points to remember

Identity

Xᵃ/Xᵇ = X⁽ ᵃ⁻ ᵇ ⁾

Xᵃ * Xᵇ = X⁽ᵃ ⁺ ᵇ⁾

(Xᵃ)ᵇ = Xᵃᵇ

To find the equivalent expression

We have, (X⁴/³ X²/³)¹/³

Using identities we can write,

(X⁴/³ X²/³)¹/³ = (X⁴/³ * X²/³)¹/³

= (X⁴/³ ⁺ ²/³)¹/³

= ( X⁽⁴⁺²⁾/³)¹/³

= (X⁶/³)¹/³

= (X²)¹/³

= X²/³

Therefore the correct answer is X²/³

User Isa A
by
6.1k points